Access to Health Information. Editorial - Kulikowski, C.; Geissbuhler, A. (Yearbook of Medical Informatics, 2008)
Objectives To provide an editorial introduction to the 2008 IMIA Yearbook of Medical Informatics with an overview of its contents and contributors.MethodsA brief overview of the main theme of “Access to Health Information”, and an outline of the purposes, contents, format, and acknowledgment of contributions for the 2008 IMIA Yearbook.Results This 2008 issue of the IMIA Yearbook highlights how Access to Health Information has become ubiquitous over the web during the past decade, with a significant number of publications in biomedical and health informatics addressing both the science and technology of the field and how it is contributing to the improvement of health systems worldwide through a number of original contributions, and selected excellent papers published during the past 12 months.Conclusion The reviews and surveys on the main research fields in medical informatics in the Yearbook provide an overview of progress during this fortieth year of IMIA, focusing on the critical role that informatics plays in access to health information.
Keywords: Editorial; 2008 IMIA Yearbook of Medical Informatics; access to health information; surveys of biomedical informatics; reviews of biomedical informatics; history of biomedical informatics; IMIA and its societies